PENGARUH KEEFEKTIFAN PENGENDALIAN INTERNAL, KESESUAIAN KOMPENSASI, DAN KEADILAN DISTRIBUTIF TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Satuan Kerja Perangkat Daerah Kota Pekanbaru) - Ray Farandy; Emrinaldi Nur DP; Hariadi Yasni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to examine (1) the effect of internal control effectiveness on tendency accounting fraud, (2) the effect of internal control effectiveness on tendency accounting fraud through job satisfaction, (3) the effect of compensation suitability on tendency accounting fraud,(4) the effect of compensation suitability on tendency accounting fraud through job satisfaction, (5) the effect of distribution justice on tendency accounting fraud, and (6) the effect of distribution justice on tendency accounting fraud through job satisfaction. The sample on this study are all of SKPD in Pekanbaru city 2016. There are 17 departments that used as a samples. Hipotesist in this study are tested using Partial Least Square (PLS) program ver. 2.0. The samples in this study were choosen using pusposive sampling method. This study used a primer datas obtained through questionnaires given to chief financial officer, chief financial subpart and 2 staff that work at financial office. From 68 sets questionnaires distributed, 64 sets questionnaires returned and analyzed. The result of direct examination in this study found that internal control effectiveness, compensation suitability directly effect the tendency accounting fraud, meanwhile distribution justice does not directly effect the tendency accounting fraud. The indirect examination found that internal control effectiveness, compensation suitability, and distribution justice effect the tendency accounting fraud through job satisfaction as an intervening variable.Keywords: Internal Control Effectiveness, Compensation Suitability, Distribution Justice, Tendency Accounting Fraud and Job Satisfaction